The role and mechanism of vascular wall cell ion channels in vascular fibrosis remodeling - Xiaolin Zhang; Hai Tian; Cheng Xie; Yan Yang; Pengyun Li; Jun Cheng (Taylor & Francis Group, 2024)
Fibrosis is usually the final pathological state of many chronic inflammatory diseases and may lead to organ malfunction. Excessive deposition of extracellular matrix (ECM) molecules is a characteristic of most fibrotic tissues. The blood vessel wall contains three layers of membrane structure, including the intima, which is composed of endothelial cells; the media, which is composed of smooth muscle cells; and the adventitia, which is formed by the interaction of connective tissue and fibroblasts. The occurrence and progression of vascular remodeling are closely associated with cardiovascular diseases, and vascular remodeling can alter the original structure and function of the blood vessel. Dysregulation of the composition of the extracellular matrix in blood vessels leads to the continuous advancement of vascular stiffening and fibrosis. Vascular fibrosis reaction leads to excessive deposition of the extracellular matrix in the vascular adventitia, reduces vessel compliance, and ultimately alters key aspects of vascular biomechanics. The pathogenesis of fibrosis in the vasculature and strategies for its reversal have become interesting and important challenges. Ion channels are widely expressed in the cardiovascular system; they regulate blood pressure, maintain cardiovascular function homeostasis, and play important roles in ion transport, cell differentiation, proliferation. In blood vessels, different types of ion channels in fibroblasts, smooth muscle cells and endothelial cells may be relevant mediators of the development of fibrosis in organs or tissues. This review discusses the known roles of ion channels in vascular fibrosis remodeling and discusses potential therapeutic targets for regulating remodeling and repair after vascular injury.